PENGARUH INFLASI, NILAI TUKAR RUPIAH, JUMLAH UANG BEREDAR (JUB), DAN JAKARTA ISLAMIC INDEX (JII) TERHADAP NILAI AKTIVA BERSIH REKSADANA SYARIAH SAHAM - Anissa Chusnul Kusumawardhani; Hery Hermawan; Arini Wildaniyati (Universitas Merdeka Madiun, 2022)
This study aims to determine the effect of Inflation, Rupiah Exchange Rate, Total Money Supply, and Jakarta Islamic Index on Net Asset Value (NAV) of Islamic Stock Mutual Funds. The population in this study is the Net Asset Value of Islamic Stock Mutual Funds available at PT Bareksa Portal Investasi and registered with the OJK in 2015-2020. The method in this study uses purposive sampling, in order to obtain a sample of 13 Islamic Stock Mutual Funds. The data used in this study is secondary data collected with quarterly report data collection techniques available on the official website from 2015-2020. This study uses quantitative methods. Data analysis was performed using multiple linear regression analysis and classical assumption test. The results of the study show that (1) there is no effect of Inflation on the Net Asset Value (NAV) of Islamic Stock Mutual Funds in 2015-2020, (2) there is an effect of Rupiah Exchange Rate on the Net Asset Value (NAV) of Islamic Stock Mutual Funds in 2015-2020, (3) there is an effect of Total Money Supply on the Net Asset Value (NAV) of Islamic Stock Mutual Funds in 2015-2020, (4) there is an effect of Jakarta Islamic Index on the Net Asset Value (NAV) of Islamic Stock Mutual Funds in 2015-2020 and there is a simultaneous effect of Inflation, Rupiah Exchange Rate, Total Money Supply, and Jakarta Islamic Index on Net Asset Value (NAV) of Islamic Stock Mutual Funds in 2015-2020.